2013
DOI: 10.1038/ncomms3889
|View full text |Cite
|
Sign up to set email alerts
|

Low paternal dietary folate alters the mouse sperm epigenome and is associated with negative pregnancy outcomes

Abstract: Epidemiological studies suggest that a father’s diet can influence offspring health. A proposed mechanism for paternal transmission of environmental information is via the sperm epigenome. The epigenome includes heritable information such as DNA methylation. We hypothesize that the dietary supply of methyl donors will alter epigenetic reprogramming in sperm. Here we feed male mice either a folate-deficient or folate-sufficient diet throughout life. Paternal folate deficiency is associated with increased birth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
322
3
11

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(351 citation statements)
references
References 69 publications
15
322
3
11
Order By: Relevance
“…17 A diet poor in folate induced DNA methylation changes in the sperm and alterations of gene expression in the placenta. 47 Using odor-induced fear conditioning in male mice, it was found that offspring also had enhanced sensitivity to the same odor, which was associated with hypomethylation at a specific olfactory receptor gene 48 . Induction of a pre-diabetic state in fathers (feeding a high fat diet in combination with streptozotocin injection) altered pancreatic gene expression pattern in male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…17 A diet poor in folate induced DNA methylation changes in the sperm and alterations of gene expression in the placenta. 47 Using odor-induced fear conditioning in male mice, it was found that offspring also had enhanced sensitivity to the same odor, which was associated with hypomethylation at a specific olfactory receptor gene 48 . Induction of a pre-diabetic state in fathers (feeding a high fat diet in combination with streptozotocin injection) altered pancreatic gene expression pattern in male offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Posttranslational histone modifications, DNA methylation patterns, and populations of small noncoding RNAs in sperm have been implicated in the transgenerational transmission of paternal experience, with changes in these epigenetic marks observed following male exposure to such diverse stimuli as stress, malnutrition, and drugs of abuse (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). In particular, the role of sperm RNA as a mechanistic link between paternal experience and its consequences on offspring behavior and physiology has been emphasized by recent studies that characterize offspring phenotypes following in vitro fertilization and/or the experimental manipulation of total sperm RNA content (12,20).…”
Section: Discussionmentioning
confidence: 99%
“…Rodent models examining paternal transmission have identified epigenetic signatures in mature sperm as possible substrates of transgenerational programming, namely patterns of retained histone modifications, DNA methylation, and/or populations of small noncoding RNAs (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21). RNA populations are of primary interest, as they may be altered through intercellular communication via epididymosomes even in transcriptionally inert mature sperm, where DNA condensation impedes other epigenetic change (22)(23)(24).…”
mentioning
confidence: 99%
“…4,[6][7][8][9][10][11][12][13] It is also increasingly becoming apparent that the environmental state of both the mother and father can underpin later diseases in offspring, even those who appear healthy at birth. [14][15][16][17][18][19][20][21][22][23][24][25][26] Such intrinsic and extrinsic factors in animal models and humans include exposure to endocrine disrupting chemicals, such as bisphenol A, phthalates, heavy metals, stress, obesity, high fat/ high caloric diets, metabolic status and starvation conditions to provide a few examples. It is also clear that in general, males may be at greater risk for later disorders, including those of the cardiovascular and neurological systems, than females.…”
Section: Introductionmentioning
confidence: 99%